Tailoring PTV expansion to improve the dosimetry of post modified radical mastectomy intensity‐modulated radiotherapy for left‐sided breast cancer patients by using 4D CT combined with cone beam CT. Issue 5 (2nd May 2021) - Zhang, Jiyong; Huang, Lei; Wu, Fangcai; Wang, Guoxi; Wu, Lili; Huang, Baotian; Lin, Yan; Li, Dongsheng; Ma, Changchun
Abstract: Purpose: Our study aimed to improve the dosimetry of post modified radical mastectomy intensity‐modulated radiotherapy (PMRM‐IMRT) for left‐sided breast cancer patients by tailoring and minimizing PTV expansion three‐dimensionally utilizing 4D CT combined with on‐board cone beam CT (CBCT). Methods: We enrolled a total of 10 consecutive left‐sided breast cancer patients to undergo PMRM‐IMRT. We measured the intra‐fractional CTV displacement attributed to respiratory movement by defining 9 points on the left chest wall and quantifying their displacement by using the 4D CT, and measured the inter‐fractional CTV displacement resulting from the integrated effect of respiratory movement, thoracic deformation and set up errors by using CBCT. We created 3 different PMRM‐IMRT plans for each of the patients using PTVt (tailored PTV expansion three‐dimensionally), PTV0.5 and PTV0.7 (isotropic 0.5‐ cm and isotropic 0.7‐ cm expanding margin of CTV), respectively. We performed paired samples t test to establish a hierarchy in terms of plan quality and dosimetric benefits. P  < 0.05 was considered statistically significant. Results: The inter‐fractional CTV displacement (2.6 ± 2.2 mm vertically, 2.8 ± 2.3 mm longitudinally, and 1.7 ± 1.2 mm laterally) measured by CBCT was much larger than the intra‐fractional one (0.5 ± 0.5 mm vertically, 0.5 ± 1.0 mm longitudinally, and 0.3 ± 0.3 mm laterally, respectively) measured by 4D CT. Intensity‐modulated radiotherapy with tailored PTV expansion based on inter‐fractional CTV displacement had dosimetrical advantages over those with PTV0.5 or those with PTV0.7 owing to its perfect PTV dose coverage and better OARs sparing(especially of heart and left lung). Conclusion: The CTV displacement in PMRM‐IMRT predominantly arises from inter‐fraction rather than from intra‐fraction during natural respiration and differs in 3 coordinate axes either inter‐fractionally or intra‐fractionally. Tailoring and minimizing PTV expansion three‐dimensionally significantly improves the dosimetry of PMRM‐IMRT for left‐sided breast cancer patients.